Sensory system for obstacle detection on high-speed lines - García, J. Jesús (2010)
This work presents an intelligent system which allows the detection of obstacles on railways. The sensory system is based on one barrier of infrared emitters and another of receivers, placed on opposing sides of the railway. Obstacle detection is achieved by a lack of reception in the detectors. The efficiency of the system is improved with the geometrical distribution of the sensory system and the encoding used at the emitting and receiving stages. Additionally optimal estimation techniques have been proposed to avoid false alarms, based on Kalman and H∞ filtering. Furthermore, Principal Component Analysis is applied to validate the obstacle detection, and to improve the efficiency of the system. A high reliability under adverse conditions is obtained with the barrier, it now being possible to detect the presence of obstacles, and to report on their position. © 2009 Elsevier Ltd.